Identifying labour market pathways after a 30-day-long sickness absence -a three-year sequence analysis study in Finland - Riku Perhoniemi; Jenni Blomgren; Mikko Laaksonen (BMC, 2023)
Abstract Background Return-to-work (RTW) process often includes many phases. Still, multi-state analyses that follow relevant labour market states after a long-term sickness absence (LTSA), and include a comprehensive set of covariates, are scarce. The goal of this study was to follow employment, unemployment, sickness absence, rehabilitation, and disability pension spells using sequence analysis among all-cause LTSA absentees. Methods Register data covered full-time and partial sickness allowance, rehabilitation, employment, unemployment benefits, and permanent and temporary disability pension (DP), retrieved for a 30% representative random sample of Finnish 18-59 years old persons with a LTSA in 2016 (N = 25,194). LTSA was defined as a ≥ 30-day-long full-time sickness absence spell. Eight mutually exclusive states were constructed for each person and for 36 months after the LTSA. Sequence analysis and clustering were used to identify groups with different labour market pathways. In addition, demographic, socioeconomic, and disability-related covariates of these clusters were examined using multinomial regressions. Results We identified five clusters with emphases on the different states: (1) rapid RTW cluster (62% of the sample); (2) rapid unemployment cluster (9%); (3) DP after a prolonged sickness absence cluster (11%); (4) immediate or late rehabilitation cluster (6%); (5) other states cluster (6%). Persons with a rapid RTW (cluster 1) had a more advantaged background than other clusters, such as a higher frequency of employment and less chronic diseases before LTSA. Cluster 2 associated especially with pre-LTSA unemployment and lower pre-LTSA earnings. Cluster 3 was associated especially with having a chronic illness before LTSA. Those in cluster 4 were on average younger and had a higher educational level than others. Especially clusters 3 and 4 were associated with a LTSA based on mental disorders. Conclusions Among long-term sickness absentees, clear groups can be identified with both differing labour market pathways after LTSA and differing backgrounds. Lower socioeconomic background, pre-LTSA chronic diseases and LTSA caused by mental disorders increase the likelihood for pathways dominated by long-term unemployment, disability pensioning and rehabilitation rather than rapid RTW. LTSA based on a mental disorder can especially increase the likelihood for entering rehabilitation or disability pension.